ANALISIS PENGARUH FAKTOR PERCEIVED USEFULLNESS, EASE OF USE DAN SIKAP TERHADAP NIAT PENGGUNAAN SOFTWARE ZAHIR ACCOUNTING - Anindya Prastiwi Setiawati; Dewi Siti Mahmudah (Fakultas Ekonomi Universitas Yos Soedarso, 2023)
This study aims to determine the effect of perceived usefulness and ease of use on the intention to use Zahir Accounting software for students of the Faculty of Economics, University of Yos Soedarso. This study used a purposive sampling technique and data analysis techniques using Structural Equation Modeling – Statistical Program for Social Science (SEM-SPSS). This study used data collection techniques using questionnaires distributed to students who use Zahir Accounting software at the Faculty of Economics, University of Yos Soedarso with a sample size of 35 students. The results of this study prove that perceived usefulness and convenience have a positive and significant effect on usability intentions.